A novel routing protocol for relay node-based energy consumption in MANET. (19th July 2019) - Sivanesan, P.
In MANET data replication play a major role for energy conservation. Redundant data transmission makes network traffic heavier and causes unnecessary energy utilisation. This paper addresses the problems due to the network traffic and unnecessary energy utilisation. It proposes the relay node-based routing protocol (RBP) to minimise the data replication and energy consumption. The relay node is implemented to collect the data from neighbours based on the stochastic process. The data is predicted by time series forecast then an error value is found. The autocorrelation function is used to compare the current variable with the predefined one (calculated error bound). If the output error value greater than predefined error value then the received data is sent to the sink as it is; otherwise the received data is discarded and the index only transmitted to the sink.